A Practicum Turn in Teacher Education - Mattsson, Matts; Eilertsen, Tor Vidar; Rorrison, Doreen; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Challenges to practicum! The authors have explored professional practice knowledge and the ways practicum is dealt with in teacher education. They report from Research and Development projects based on collaboration between universities and school communities. Empirical studies have been carried out in Australia, Canada, China, Denmark, Finland, Norway and Sweden. Communication about practicum is reframed. Preservice teachers$1 (Bexperiences during practicum serve as a point of departure for improving teacher education. The book is a must for everyone committed to quality in initial teacher education, including preservice teachers, school leaders and local supervisors. (3z(BThis volume explores new and different ways to think about the construction and evaluation of the practicum that students encounter. Contributors ask the reader to consider the assumptions that the practicum is based on, question these assumptions and strive to find new and better ways to contribute to the autonomy, professionalism, and moral development of emerging teachers. The focus is clearly on creating conversational and learning spaces for students that encourage them to think explicitly about theory and its application to practice and vice versa. The book not only challenges our thinking but also provides rich examples of research and evaluation in this area, which help us to hear the voices of those involved in the practicum in fresh and insightful ways.(3y (BReflections by Roslin Brennan Kemmis, Head of the School of Education, Charles Sturt University, Wagga Wagga, Australias
Keywords: Education; Education; Teaching and Teacher Education